Interventional therapy procedures assisted by medical imaging and simulation. The experience of U 703 INSERM (lille France) - Rousseau, J.; Vermandel, M.; Betrouni, N.; Dubois, P. (Cellular and Molecular Biology, 2007)
Since the early 1990s, minimally invasive techniques have been increasingly used in ever more and diversified fields of application. These techniques have some shared characteristics (predominant role of medical imaging, intensive use of new communication technologies, a multidisciplinary medical and scientific framework, etc.) but also shared specific problems (high-tech tools unfamiliar to the medical users, a major and long period of time for technological development, unavailability of training systems, difficulties in obtaining regulatory approval). For a long time, our Laboratory of Medical Physics (U 703 Inserm) has developed an innovative research activity in biomedical engineering in the field of assisted therapy, medical imaging and medical simulation. This paper presents the general context of interventional therapy procedures assisted by image and simulation and describes our scientific activities based on realistic objectives close to medical practice.